2017
DOI: 10.1016/j.clysa.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

El suicidio en jóvenes en España: cifras y posibles causas. Análisis de los últimos datos disponibles

Abstract: El suicidio es la tercera causa de muerte en el grupo de edad de entre los 15 a los 29 años, superado sólo por las causas externas de mortalidad y los tumores, de acuerdo con el Instituto Nacional de Estadística. En los últimos datos disponibles se pone de manifiesto que 310 niños y jóvenes menores de 30 años se quitaron la vida, lo que supone un 7.77% del total de víctimas del suicidio. El presente artículo, pretende describir profusamente el estado de la cuestión a la luz de los datos disponibles en la liter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 12 publications
1
9
0
12
Order By: Relevance
“…Regarding the prevalence of suicidal behavior, the results of the present study are very similar to those obtained in previous research, both from national and international perspectives [1][2][3]. In this study, suicide ideation was the most prevalent suicide behavior (8.2%), followed by suicide planning (5.2%) and suicide attempts (3.7%), that is, the prevalence decreased with the severity of suicidal behavior.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding the prevalence of suicidal behavior, the results of the present study are very similar to those obtained in previous research, both from national and international perspectives [1][2][3]. In this study, suicide ideation was the most prevalent suicide behavior (8.2%), followed by suicide planning (5.2%) and suicide attempts (3.7%), that is, the prevalence decreased with the severity of suicidal behavior.…”
Section: Discussionsupporting
confidence: 90%
“…Suicide is a major public health concern worldwide [1]. In Spain, suicide is the highest external cause of death in adults and the third-highest cause of death in the population aged between 15 and 29 years [2]. This is especially worrisome as recent studies have identified an increase in suicidal behavior among adolescents in recent years [3].…”
Section: Introductionmentioning
confidence: 99%
“…Gender‐differences between internalizing (e.g., mood disorders) and externalizing (e.g., conduct disorders) disorders may also be related (Boyd et al, ). The few empirical data available about gender paradox in Spain suggest similar gender trends for STB (Navarro‐Gómez, ).…”
Section: Introductionmentioning
confidence: 94%
“…In Spain in 2015, suicide was the first cause of death among 15‐ to 19‐year‐old women and the second among 20‐ to 24‐year‐old men (Instituto Nacional de Estadísticas, ). More current data shows that suicide rates among 15‐ to 29‐year‐olds represent 7.77% of the total suicide deaths in the country (Navarro‐Gómez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Al respecto, es bien conocido que el género femenino presenta mayormente síntomas de ansiedad, depresión y riesgo suicida en comparación con los hombres (Chen, 2010;Daine, Hawton, Singaravelu, Stewart, Simkin & Montgomery, 2013;Lowry, Crosby, Brener, y Kann, 2014;Lambert, Boyd, Cammack & Ialongo, 2012;Waldrop, Hanson, Resnick, Kilpatrick, Naugle & Saunders, 2007). Incluso aunque el suicidio consumado sea más frecuente en hombres que en mujeres (Navarro-Gómez, 2017). Estas diferencias algunas veces son explicadas por el procesamiento de la información emocional particular de género, el patrón de gestión emocional propio de la cultura, por el acceso a métodos más lesivos en hombres y por estrategias activas recurrentes para afrontar dificultades, menos frecuente en masculinos (Suárez & Wilches, 2015).…”
Section: Discussionunclassified